Institutional Experience and Orthoplastic Collaboration Associated with Improved Flap-based Limb Salvage Outcomes. Issue 11 (November 2021) - Hoyt, Benjamin W.; Wade, Sean M.; Harrington, Colin J.; Potter, Benjamin K.; Tintle, Scott M.; Souza, Jason M.
Abstract: Background: Flap-based limb salvage surgery balances the morbidity and complexity of soft tissue transfer against the potential benefit of preserving a functional limb when faced with a traumatized extremity with composite tissue injury. These composite tissue injuries are well suited for multidisciplinary management between orthopaedic and plastic surgeons. Thus, it makes intuitive sense that a collaborative, orthoplastic approach to flap-based limb salvage surgery can result in improved outcomes with decreased risk of flap failure and other complications, raising the question of whether this orthoplastic team approach should be the new standard of care in limb salvage surgery. Questions/purposes: (1) Is there an association between increased annual institutional volume and perioperative complications to include free and local flap failure (substantial flap viability loss necessitating return to the operating room for debridement of a major portion or all of the flap or amputation)? (2) Is an integrated orthoplastic collaborative approach to managing combat-related traumatic injuries of the extremities individually associated with a decreased risk of flap failure and overall flap-related complications? (3) What other factors, such as location of injury, injury severity score, and initial inpatient length of stay, were associated with flap necrosis and flap-related complications? Methods: We performed a retrospective review of the electronic medical records of all patients who underwent flap-based limb salvage for combat-related extremity trauma in the United States Military Health System's National Capital Region between January 1, 2003 and December 31, 2012. In total, 307 patients underwent 330 flap procedures. Of the 330 flaps, 59% (195) were local or pedicled flaps and 41% (135) were free flaps. Patients were primarily male (99% [303]), with a median (interquartile range) age of 24 years old (IQR 21 to 29), and 87% (267 of 307) of injuries were sustained from a blast mechanism. We collected data on patient demographics, annual case volume involving flap coverage of extremities, mechanism of injury, flap characteristics, perioperative complications, flap failure, flap revision, isolated orthopaedic management versus an integrated orthoplastic approach, and other salvage procedures. For the purposes of this study, orthoplastic management refers to operative management of flap coverage with microvascular surgeons present for soft tissue transfer after initial debridement and fixation by orthopaedic surgery. The orthoplastic management was implemented on a case-by-case basis based on individual injury characteristics and the surgeon's discretion with no formal starting point. When implemented, the orthoplastic team consisted of an orthopaedic surgeon and microvascular-trained hand surgeons and/or plastic surgeons. In all, 77% (254 of 330) of flaps were performed using this model. We considered perioperative flap complications as any complication (such as infection, hematoma, dehiscence, congestion, or necrosis) resulting in return to the operating room for re-evaluation, correction, or partial debridement of the flap. We defined flap failure as a return to the operating room for debridement of a major portion of the flap or amputation secondary to complete or near-complete loss of flap viability. Of the flap procedures, 12% (40 of 330) were classified as a failure and 14% (46 of 330) experienced complications necessitating return to the operating room. Over the study period, free flaps were not more likely to fail than pedicled flaps (11% versus 13%; p = 0.52) or have complications necessitating additional procedures (14% versus 16%; p = 0.65). Results: Our multiple linear regression model demonstrated that an increased number of free flaps performed in our institution annually in any given year was associated with a lower likelihood of failure per case (r = -0.17; p = 0.03) and lower likelihood of reoperation for each flap (r = -0.34; p < 0.001), after adjusting for injury severity and team type (orthoplastic or orthopaedic only). We observed a similar relationship for pedicled flaps, with increased annual case volume associated with a decreased risk of flap failure and reoperation per case after adjusting for injury severity and team type (r = -0.21; p = 0.003 and r = -0.22; p < 0.001, respectively). Employment of a collaborative orthoplastic team approach was associated with decreased flap failures (odds ratio 0.4 [95% confidence interval 0.2 to 0.9]; p = 0.02). Factors associated with flap failure included a lower extremity flap (OR 2.7 [95% CI 1.3 to 6.2]; p = 0.01) and use of muscle flaps (OR 2.3 [95% CI 1.1 to 5.3]; p = 0.02). Conclusion: Although prior reports of combat-related extremity trauma have described greater salvage success with the use of pedicled flaps, these reports are biased by institutional inexperience with free tissue transfer, the lack of a coordinated multiservice effort, and severity of injury bias (the most severe injuries often result in free tissue transfer). Our institutional experience, alongside a growing body of literature regarding complex extremity trauma in the civilian setting, suggest a benefit to free tissue coverage to treat complex extremity trauma with adequate practice volume and collaboration. We demonstrated that flap failure and flap-related complications are inversely associated with institutional experience regardless of flap type. Additionally, a collaborative orthoplastic approach was associated with decreased flap failures. However, these results must be interpreted with consideration for potential confounding between the increased case volume coinciding with more frequent collaboration between orthopaedic and plastic surgeons. Given these findings, consideration of an orthoplastic approach at high-volume institutions to address soft tissue coverage in complex extremity trauma may lead to decreased flap failure rates. Level of Evidence: Level III, therapeutic study.